STUDI FENOMENOLOGI PERSONAL BRANDING PENDAKI GEN-Z DI MEDIA SOSIAL - Adani, Naufal Sallahudin; Setianingrum, Vinda Maya (The Commercium, 2024)
This research highlights the importance of personal branding, which is the process of creating a self-image to increase an individual's selling value. In the digital era, social media such as Instagram has become a primary tool in forming personal branding. Generation Z, who are active in mountain climbing, utilizes this platform to share experiences and build self-identity. This trend reflects how the hobby of climbing is used as a means of self-expression and social interaction. Using Montoya's personal branding theory, this study found that the aspects of "visible," "specialization," and "unity" were very prominent in the concept of personal branding used. The interviewees utilized Instagram to show their presence, showcase special skills, and maintain consistency between online images and real behavior, all of which contributed to a strong self-image in the eyes of their audience. However, concepts such as "firmness," "personality," "difference," "leadership," and "good name" have not been fully explored. The research method used a qualitative approach, specifically phenomenological studies, to explore the experiences of generation Z in forming personal branding through Instagram. Data were collected through in-depth interviews with young climbers who are active on social media. These results show that Instagram is an important platform for Generation Z mountain climbers in building and managing their personal branding, with audience feedback playing a significant role in driving the development of this branding.